Perkembangan Literatur Hadis Masa Awal Pembukuan: Kajian atas Kitab Al-Mushannaf Abdurrazaq sebagai Dokumen Otentik Hadis Abad Pertama - Alwy, Moh. Fazrul Azrif (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2021)
Hadith literature is a very important thing in the process of studying a hadith. Therefore, the process of developing literature must be studied either historically or scientifically. It is said that there are several periods in it, including: Pre-Codification; Codification; Post Codification; Presentation, collection, pen knowledge, and discussion. But before that, it is necessary to look at the development of hadith literature in the Mecca and Medina periods. One of the literary products during the codification period was the book al-Mushannaf Abdurrazaq. This book has been studied by many Muslim scholars as well as Western scholars (orientalists). Harald Motzki even focused his study on this book to find authentic sources of hadith in the first century of Hijri as an epistemological basis for sources of Islamic law after the Qur'an. The question arises, how is the authenticity of the hadith in the book al-Mushannaf Abdurrazaq? What approach did Harald Motzki use in studying the book? The findings in this study that Dating that Harald Motzki did to the book Al-Mushannaf Abdurrazzaq, using the isnad cum analysis method and the traditional-historical approach shows evidence that the materials Abd ar-Razzaq relied on the four main informants were authentic. Therefore, the book is considered as an authentic hadith document of the first century of Hijriyah, as well as clear evidence that Islamic law has existed since that time.